The Geological Investigation of the Lunar Reiner Gamma Magnetic Anomaly Region - Junhao Hu; Jingwen Liu; Jianzhong Liu; Jiayin Deng; Sheng Zhang; Danhong Lei; Xuejin Zeng; Weidong Huang (Remote Sensing)
Reiner Gamma is a potential target for low-orbiting spacecraft or even surface-landed missions in the near future. Unfortunately, thus far, no comprehensive low-altitude (below 20 km) or surface measurements of the magnetic field, magnetic source and plasma environment have been made post-Apollo to complement and complete our understanding of the solar wind interaction with lunar magnetic anomalies and swirl formation. Acquiring the detailed geological knowledge of the Reiner Gamma region is significant for the above scientific targets. In this study, the following research work in the lunar Reiner Gamma magnetic anomaly region was carried out for the regional geological investigation: (1) topographic and geomorphologic analysis; (2) element, mineral, and sequence analysis; and (3) a 1:10,000 regional geological map analysis. Our work helps define measurement requirements for possible future low-orbiting or surface-landed missions to the Reiner Gamma area or similarly magnetized regions of the lunar surface.